Volume 4A: Combustion, Fuels, and Emissions 2020
DOI: 10.1115/gt2020-14583
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fuel and Load Flexibility in a SGT-600/700/800 Burner Under Atmospheric Pressure Conditions Using High-Speed OH-PLIF and OH Chemiluminescence Imaging

Abstract: Fuel and load flexibility have been increasingly important features of industrial gas turbines in order to meet the demand for increased utilization of renewable fuels and to provide a way to balance the grid fluctuations due to the unsteady supply of wind and solar power. Experimental investigations were performed using a standard 3rd generation dry low emission (DLE) burner under atmospheric pressure conditions to study the effect of central and pilot fuel addition, load variations and hydrogen (H2) enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Many researchers have observed that the addition of hydrogen to natural gas leads to a transition in flame shape from a V-shape to an M-shape, although with different effects on dynamic instabilities [63,72,[75][76][77]. Referring back to Figure 4 from the work of Shanbhogue et al [75], it can be observed that the 100% CH 4 flame at φ = 0.58 exhibited a V-shape and was reported as being thermoacoustically stable.…”
Section: Effect On Flame Structure and Flame Positionmentioning
confidence: 96%
See 3 more Smart Citations
“…Many researchers have observed that the addition of hydrogen to natural gas leads to a transition in flame shape from a V-shape to an M-shape, although with different effects on dynamic instabilities [63,72,[75][76][77]. Referring back to Figure 4 from the work of Shanbhogue et al [75], it can be observed that the 100% CH 4 flame at φ = 0.58 exhibited a V-shape and was reported as being thermoacoustically stable.…”
Section: Effect On Flame Structure and Flame Positionmentioning
confidence: 96%
“…The lower pressure amplitudes observed for the hydrogen-rich flame coincided with a reduction in the observed flame front fluctuations compared to the pure natural gas flame. Subash et al [76] extended the work of Lantz et al [72] by comparing the dynamics of pure natural gas and pure hydrogen flames using an optimised version of the same DLE burner. The pure hydrogen flame was shorter, more compact and stabilised closer to the burner exit compared to the pure methane flame.…”
Section: Effect On Flame Structure and Flame Positionmentioning
confidence: 99%
See 2 more Smart Citations